A agricultura ecológica realizada em Remígio, PB: um estudo sobre produção de conhecimento e inovação - Farias, Alexandra Leite de (2017)
The general objective of this dissertation was perform a study on innovation and knowledge production between organic farmers unionised in the county of Remígio, PB, located in the micro-region of Paraíba Western Curimataú, belonging to Borborema’s Pole, which is formed by a network of 14 syndicates of rural workers (SRWs). The pole for 21 years has been practicing respectful agriculture on an ecological basis, prioritizing existing social relations. The specific aiming of this study are: (I) Knowing the production of agroecological knowledge and innovations based in the county of Remígio, PB, resulting from the partnership with the Borborema Pole; (II) Identify the news with the transition processes socio-technical; (III) To know the trajectory of the familiar farmers in the matter of the ecological transition of agriculture and its relation with innovation and production of knowledge. Methodologically, we opted for the qualitative approach and the case study. We performed the data collection through a semi-structured interview. Data collection occurs through 20 interviews. We used two types of scripts in the interviews: a script to the farmers and another one for technicians. The main results indicate that the ecological agriculture practiced in the county of Remígio is a private and advanced process of local development. The “local aspect” and “particular” reference themselves to the important characteristic that is the aspect of innovation, from the experience and the necessity of each farmer, respecting his particularity. This process of knowledge and innovations producing is essentially based on reflective practice and the contextualization of knowledge through everyday/informal processes of innovation. As important innovations that arise through these processes, they are the several techniques and actions implemented, such as seed banks, solidarity funds, etc. In addition to taking the innovative role, the awareness and the growing change in farmers' thinking. Some of these innovations are configured as novelties since they are based on external models. The historical path allows us to affirm the presence of all these innovations produced as alternatives to the ecological transition of the productive units. I conclude by reaffirming the rich process of innovations and knowledge now produced by these ecological farmers in communion with the organizations, many positive points achieved mainly in the reaffirmation of these farmers and in the valorization of their identities.